2019
DOI: 10.1016/j.jhealeco.2019.102228
|View full text |Cite
|
Sign up to set email alerts
|

Medical innovation, education, and labor market outcomes of cancer patients

Abstract: Innovations in cancer treatment have lowered mortality, but little is known about their economic benefits. We assess the effect of two decades of improvements in cancer treatment options on the labor market outcomes of breast and prostate cancer patients. In addition, we compare this effect across cancer patients with different levels of educational attainment. We estimate the effect of medical innovation on cancer patients' labor market outcomes employing tax return and cancer registry data from Canada and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…For instance, we observe that highly educated individuals are more likely to have accidents classified as “Accidental exposure to other/unspecified factors,” a catch‐all category for likely less severe accidents, whereas individuals with low levels of education are more likely to suffer “Exposure to inanimate mechanical forces,” likely work accidents (see the Supplementary Appendix). This suggestive evidence could provide context to findings such as in Heinesen and Kolodziejczyk (2013) and Jeon and Pohl (2019), who estimate an educational gradient in the employment effects of cancer diagnoses. However, we do not find evidence of a large differential effect of accidents on labor market outcomes across education groups.…”
Section: Discussionsupporting
confidence: 76%
“…For instance, we observe that highly educated individuals are more likely to have accidents classified as “Accidental exposure to other/unspecified factors,” a catch‐all category for likely less severe accidents, whereas individuals with low levels of education are more likely to suffer “Exposure to inanimate mechanical forces,” likely work accidents (see the Supplementary Appendix). This suggestive evidence could provide context to findings such as in Heinesen and Kolodziejczyk (2013) and Jeon and Pohl (2019), who estimate an educational gradient in the employment effects of cancer diagnoses. However, we do not find evidence of a large differential effect of accidents on labor market outcomes across education groups.…”
Section: Discussionsupporting
confidence: 76%
“…Out of the 25 selected articles, 7 original definitions of innovation were retrieved [17][18][19][20][21][22][23] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Lag effect should be taken into consideration when testing the impact of pharmaceutical manufacturing innovation on perceived health. There should be a lag effect between pharmaceutical manufacturing innovation and perceived health, because there is also a time lag from the moment when a drug was approved to the moment when it really worked ( 42 , 43 ). Lichtenberg ( 44 ) found that premature mortality in Canada is associated with at least 10-year cumulative use of drugs.…”
Section: Resultsmentioning
confidence: 99%